(3GdeeGQSI GdOjebQGWjI ddSdWI (B:s (3Hjf GdfXQjI h GdhGbY (B/s - (3Hf MehOI,HhYdGe s ((3GdLRGFQ (B:s (3OGQ GdCeI ddfTQ h GdJhRjY ,s)
(3jJWQb Zdi ehGVjY MSGSI JTZd Hcd GdTYhH h cd GdGfXeI aj GdYGde gd JhLO OjebQGWjI MbjbjI(B. (3gd JDOj GdeLGdS GdefJNHI OhQgG ceG jfHZj (B-(3cja jbhe QFjS GdLeghQjI HhGLHg GdJGQjNj (B-(3eGgh GSdhH dYed GdMcheI (B. (3cja JVef GSJbdGd GdbVGA (B-(3ef jSgQ Ydi GMJQGe GdOSJhQ h cja (B-(3cja JJYGed GdSdYI eY GdeMjW GdeJeKd aj GdLjT h GdJjGQ s
Keywords: (3GdOjebQGWjIs; (3GdSdWIs